Public engagement in rural aging communities - Denker, Amy E. (Kansas State University, 2014)
Public engagement in rural, aging communities is often an after thought when creating plans, strategies, or projects in these communities. Initiatives that focus specifically on interacting with aging ruralites through new media is almost non-existent. However, engagement through web-based forums or social media is a growing trend. At the same time, older people have proven that they do not use the internet or social media as frequently as younger generations. To bridge the gap of inexperience with online forms of engagement, I investigate whether educational components introduced through traditional face-to-face forms of public engagement can increase the participation of older residents. To test this, I introduce social media and online engagement to older adults through an educational presentation at a public meeting in Council Grove, Kansas, in cooperation with the Flint Hills Regional Council. I monitored social media and online websites connected to the public meeting prior to and after the meeting to track changes in engagement that occurred due to the meeting. Though there was little change in engagement on the two websites I monitored, the survey results suggest that the people at the meeting appreciated the introduction and did have some familiarity with the internet and the online engagement environments. Unfortunately, this research does not definitively answer the question asked. It suggests that further education presented in future meetings may increase online engagement when implemented at a larger scale.
Keywords: Rural Public Engagement; Aging (0493)